2004
DOI: 10.1002/polb.10690
|View full text |Cite
|
Sign up to set email alerts
|

Studies of photooxidative degradation of poly(vinyl chloride)/poly(ethylene oxide) blends

Abstract: The photooxidative degradation of blends (in a full range of compositions) of amorphous poly(vinyl chloride) (PVC) with semicrystalline poly(ethylene oxide) (PEO) in the form of thin films is investigated using absorption spectroscopy (UVvisible and Fourier transform infrared) and atomic force microscopy (AFM). The amount of insoluble gel formed as a result of photocrosslinking is estimated gravimetrically. It is found that the PVC/PEO blendsí susceptibility to photooxidative degradation differs from that pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
0
28
0
1
Order By: Relevance
“…Alguns tipos de polímeros, como o polietileno, polipropileno, poliestireno e poli(tereftalato de etileno), foram extensivamente estudados ao longo dos anos, e os mecanismos de fotodegradação e fotoestabilização, bem como os fatores que controlam a cinética do processo e mudanças nas propriedades do produto estão razoavelmente bem estabelecidos [7][8][9][10][11][12][13][14] . Enquanto isso, no caso de blendas poliméricas, poucos estudos na área de fotodegradação podem ser encontrados na literatura [15][16][17][18] . Polipropileno (PP) e o poliestireno de alto impacto (HIPS) são usados em larga variedade de produtos.…”
Section: Introductionunclassified
“…Alguns tipos de polímeros, como o polietileno, polipropileno, poliestireno e poli(tereftalato de etileno), foram extensivamente estudados ao longo dos anos, e os mecanismos de fotodegradação e fotoestabilização, bem como os fatores que controlam a cinética do processo e mudanças nas propriedades do produto estão razoavelmente bem estabelecidos [7][8][9][10][11][12][13][14] . Enquanto isso, no caso de blendas poliméricas, poucos estudos na área de fotodegradação podem ser encontrados na literatura [15][16][17][18] . Polipropileno (PP) e o poliestireno de alto impacto (HIPS) são usados em larga variedade de produtos.…”
Section: Introductionunclassified
“…The miscibility of the PVC/PEO blend was explained as a result of donor-acceptor interactions between the chlorine atoms of PVC, as a weak acceptor species, and oxygen atoms of the PEO, as a donor species. Kaczmarek et al 19 had a similar conclusion with the exception that interactions are possible because PEO is a proton-accepting agent (due to the ether atom in each unit) and PVC is a proton-donating polymer (because of α-hydrogen atoms). On the other hand, by differential scanning calorimetry and viscosimetric analyses, Ramesh et al 2 showed that the PVC/PEO blends are fully miscible.…”
Section: Introductionmentioning
confidence: 66%
“…7 Miscibility, mechanical, optical, morphological, and thermal properties of PVC/PEO blends have already been studied in the literature. [2][3][4][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, data on the miscibility of PVC and PEO are contradictory. Margaritis and Kalfoglou 10 found that PVC and PEO were miscible for PVC-rich blends according to results obtained by dynamic mechanical analysis, differential scanning calorimetry, and optical microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of oxygen UV-irradiation causes photooxidation of polymeric films [22][23][24]. Chain scission and cleavage of chemical bonds lead to the formation of free radicals, which can react with oxygen from air and produce peroxide radicals and then they can react with polymer.…”
Section: Resultsmentioning
confidence: 99%